Development of Thermoelectric generator based on Ionic Liquids for high temperature applications. (2018) - Laux, Edith; Uhl, Stefanie; Gauthier, Nicolas; Jeandupeux, Laure; Keppner, Herbert; Pérez López, Pilar; Pauline, Sanglard; Vanoli, Ennio; Marti, Roger
Abstract: Current, Seebeck-coefficients (SE ) and maximal power output (Pmax ) of thermoelectric generators using Ionic Liquids (ILs) were measured to determine the optimal temperature window for their use as thermoelectric generators (TEGs) in the range between room temperature (RT) and 300°C. The IL was sandwiched in a thermoelectric cell between a heated and a cooled electrode, allowing temperature-dependent current, voltage, and power-output characterization. Dissolving redox-couples (e.g. I2 /I - ) enables charge transfer from the IL to the electrode. It was found, that protic ILs degraded irreversibly at 140°C. Aprotic ILs, however, in combination with LiI/I2 redox couples exhibit higher temperature stability being finally limited either by redox-couple-electrode reactions, by temperature-induced redox couple degradation or by reaching at the boiling point at about 280°C. ILs being solid at room temperature could successfully be activated, as soon as at least the hot electrode of the set-up was heated above the melting point (m.p.) of the IL. As a striking observation, the thermo-voltage (linked to the SE ) changes the sign as soon as the cold electrode was kept below the m.p. when Ethylammonium tetrafluoroborate (EA BF4) was used. Another IL, Tetrabutylammonium tetrafluoroborate (TBA BF4) exhibited in the full temperature range negative SE as high as 7 mV/K.